1999
DOI: 10.1046/j.1365-2133.1999.02836.x
|View full text |Cite
|
Sign up to set email alerts
|

Circumferential fingernail

Abstract: We describe a Brazilian girl with a congenital circumferential nail on her left ring finger associated with other bony and soft tissue abnormalities of the affected limb. The tubular nail plate resembling a punch biopsy has been described as a circumferential nail, an extremely rare congenital malformation that can be associated with other congenital anomalies. In our review of the literature, there have only been two previous reports of this unusual condition affecting the fingernails.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 14 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…Rider [1992] reported on an infant with CPP who had skeletal abnormalities of the forearms. Our patients manifest the combination of anomalies reported by Alves et al [1999], but separately present in the proposita and her sister. Ulnar involvement with CPP in the proposita and ulnar ray digit deficiency and ulnar agenesis in his sister are primarily postaxial defects [Temtamy and McKusick, 1978].…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…Rider [1992] reported on an infant with CPP who had skeletal abnormalities of the forearms. Our patients manifest the combination of anomalies reported by Alves et al [1999], but separately present in the proposita and her sister. Ulnar involvement with CPP in the proposita and ulnar ray digit deficiency and ulnar agenesis in his sister are primarily postaxial defects [Temtamy and McKusick, 1978].…”
Section: Discussionmentioning
confidence: 79%
“…Both conditions have been separately observed in different members of the same family studied by Westgate and Holmes [1994], and in an other family with a double nail on the 5th toe [Temtamy and McKusick, 1978]. CPP with deficiency limb defects was reported by Alves et al [1999] in a Brazilian girl with congenital circumferential nail on her left 4th finger and an incomplete cleft between the index and middle fingers (i.e., ectrodactyly). These authors also found a hypoplastic 4th finger with heterotopic dorsal skin, short ulna, over-riding radius, and a dislocated radial head on radiographs.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations